Distribution and Carbon Sequestration Potential of Cola laurifolia Mast.: A Dominant Native Riparian Species along Permanent Rivers in Sub-Saharan Africa - Gouwidida Elice Kabore; Philippe Bayen; Sidzabda Djibril Dayamba; Adjima Thiombiano (European Scientific Journal, ESJ, 2023)
The continuously increasing interest in carbon market call for adequate approaches to assess and monitor the growth and carbon of tree species. Species-specific models for estimating aboveground biomass (AGB) are the accurate means of quantifying species’ carbon pools. This study aimed at developing allometric equation for Cola laurifolia Mast., a dominant and multi-purpose riparian species along the Mouhoun River in Burkina Faso. The study first used a destructive sampling approach on thirty trees individuals of different diameter classes after collecting their dendrometric data. Explanatory parameters used to build the models were tree diameter at breast height (Dbh), basal diameter at 20 cm (D20), height (H), and mean crown diameter (MCd). Model development involved looking at different forms of models and different compartments of the tree (leaves, branches, stems and total above ground biomass). Subsequently, field inventory data were collected in protected and communal areas along three zones of the Mouhoun river (upstream, midstream and downstream) to assess and compare the carbon stock in the different areas and also characterize their population (assessment of regeneration status of the species). The results showed that the log-log linear model was the best-fitted form for the three tree compartments (i.e., leaf, branch, stem) and the total AGB, and incorporated Dbh and H as predictors. The total AGB model was more accurate with the highest goodness of fit (high R2) low residual standard error (RSE) (R²=0.92; RSE=0.28) as compared to the three component models. Nevertheless, all the allometric equations established for the prediction of leaves, stem, branches and total aboveground biomass were statically significant (p≤0.0001). The study also showed that the population structure of the species reflects a low regeneration potential along the studied river zones (i.e., upstream, intermediate and downstream zones), calling for initiatives to address the issue. The carbon stock was found to be 56.40 kg C tree-1 and 9.24 Mg C. ha-1. The density of C. laurifolia was higher in downstream zone, and consequently the carbon stock was higher in these areas. The study also compared the outputs from existing generalized allometric models to our newly developed specific-equation and found that they overestimate or underestimate the carbon stock of C. laurifolia. The results confirm the value of species-specific model which therefore calls for more effort to develop such models for all dominant species for greater accuracy in AGB estimations at scale.